Is the Pastoral Ministry Bad for One’s Spiritual Health?: Insights from an Eighteenth-Century English Sermon - Sorenson, Eric (Journal of spiritual formation & soul care, 2018)
It was a universal conviction among the leaders of the ancient church that vocational ministry is attended by certain spiritual hazards that threaten to undo the very soul of the minister. This notion is revived in William Paley’s 1795 sermon, “Dangers Incidental to the Clerical Character.” The pastoral ministry, he warns, is comprised of “dangers inherent to the very nature of our profession.” In this ordination sermon, Paley not only identifies certain spiritual hazards, but he traces their roots to the unique context and responsibilities of daily ministry. A close reading of Paley’s sermon highlights its clear relevance to ministers in the twenty-first century, who, like all ministers throughout the history of the church, are constantly exposed to the spiritual dangers lurking in ministry itself. Such a close reading also reveals practical means by which today’s minister can be constantly vigilant to overcome these dangers.